Psychostimulant Drugs Abuse among Libyan Medical Students (British Journal of Multidisciplinary and Advanced Studies, 2023)
The psychostimulant substances were used by medical students is a phenomenon partially well-known. The aim of present work was to find the prevalence of use and abuse of psychostimulant drugs among medical students. A descriptive cross sectional study was conducted A structured questionnaire about potential use of caffeine, nicotine, and amphetamine as psychostimulant drugs use, was distributed by electronic means (google forms), among medical students from various levels at different faculties from 18 Libyan medical universities. A total of 752 students responded to the study. About 81.6% of respondents were caffeine users, 13.4% smokers and 6.8% were amphetamines consumers. More than 50% of Caffeine consumers reported increase in their caffeine consumption after started their university studies and 66.9% of nicotine consumers reported increase in nicotine consumption after started their university studies while 81.1% of amphetamine consumers reported that taking amphetamine only since they have started the university studies. About 73.5% of respondents have consume caffeine mainly during examination period.  Furthermore, nicotine consumers reported different reasons for being smokers. About 52% of amphetamine consumers abuse amphetamine mainly during examination period. Nearly 47.3% of caffeine consumers reported their intention to quit caffeine intake but only 24.3% succeeded to quit. Similarly, 64.4% of nicotine consumers reported their intention to quit smoking but only 25.4% of them succeeded to quit. For amphetamine consumer approximately 39.4% have intention to quit amphetamine intake however only about 27.8% of them succeeded to quit. The use of psychostimulant substances by medical students in Libya is a phenomenon that should be evaluated systematically due to its prevalence and potential impact.